2019
DOI: 10.1021/acsomega.9b01601
|View full text |Cite
|
Sign up to set email alerts
|

If You Cannot Win Them, Join Them: Understanding New Ways to Target STAT3 by Small Molecules

Abstract: Signal transducer activator of transcription 3 (STAT3) is among the most investigated oncogenic transcription factors, as it is highly associated with cancer initiation, progression, metastasis, chemoresistance, and immune evasion. Evidences from both preclinical and clinical studies have demonstrated that STAT3 plays a critical role in several malignancies associated with poor prognosis such as glioblastoma and triple-negative breast cancer, and STAT3 inhibitors have shown efficacy in inhibiting cancer growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…STAT3 dimerization is carried out by its SH2 domain, as SH2 domain from one STAT3 monomer associates with the phosphorylated Y705 located in the transactivation domain of another STAT3 monomer. 29 We demonstrate that MST2‐mediated phosphorylation at STAT3 T622 dampened the STAT3 dimerization, thereby inhibiting STAT3 activation. Further, prostate cancer cells harboring STAT3 T622A grew much faster than the WT cells, and patients with a high level of STAT3 T622 phosphorylation showed a longer average survival time.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…STAT3 dimerization is carried out by its SH2 domain, as SH2 domain from one STAT3 monomer associates with the phosphorylated Y705 located in the transactivation domain of another STAT3 monomer. 29 We demonstrate that MST2‐mediated phosphorylation at STAT3 T622 dampened the STAT3 dimerization, thereby inhibiting STAT3 activation. Further, prostate cancer cells harboring STAT3 T622A grew much faster than the WT cells, and patients with a high level of STAT3 T622 phosphorylation showed a longer average survival time.…”
Section: Discussionmentioning
confidence: 76%
“…STAT3 strongly binds to DNA when it is in the dimeric form. STAT3 dimerization is carried out by its SH2 domain, as SH2 domain from one STAT3 monomer associates with the phosphorylated Y705 located in the transactivation domain of another STAT3 monomer 29 . We demonstrate that MST2‐mediated phosphorylation at STAT3 T622 dampened the STAT3 dimerization, thereby inhibiting STAT3 activation.…”
Section: Discussionmentioning
confidence: 80%
“…BBI608 (Napabucasin) is a small molecule that can bind to the STAT3 protein, limiting its cellular activity. Zaraquiey et al [64] mapped the binding site and characterized the binding mode of NNI608 at STAT3, which resembles the effect of a D570K mutation in a linker domain known to interrupt STAT3 activity [65]. Han et al [66] reported that BBI608 treatment significantly blocked GBM cells' (U87 and LN229 cell lines) proliferation, migration, invasion, and sphere formation.…”
Section: Stat3 Inhibitors As Drug Candidates For Gbm Therapymentioning
confidence: 99%